2023
DOI: 10.1039/d3cp01074k
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive pulsed gas–liquid discharge in different atmospheres: from discharge characteristics to plasma–liquid interactions

Xu Lu,
Li Zhang,
Sen Wang
et al.

Abstract: Intense Ar spark discharge leads to the most efficient plasma–liquid interactions, energetic He particles give rise to multiple synthesis pathways for H2O2, and OH plays different roles in aqueous physicochemical reactions in different atmospheres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The concentration of long-lived reactive species was quantified using a UV-vis spectrophotometer (Jinghua, UV1800, China), as previously described in references [24,25]. The degradation products at different treatment times are analyzed by liquid chromatography-mass spectrometry (LC-MS, Agilent, 1290UPLC/Q-TOF6550).…”
Section: Experimental Setup Of Plasma Source and Tetracycline Degrada...mentioning
confidence: 99%
“…The concentration of long-lived reactive species was quantified using a UV-vis spectrophotometer (Jinghua, UV1800, China), as previously described in references [24,25]. The degradation products at different treatment times are analyzed by liquid chromatography-mass spectrometry (LC-MS, Agilent, 1290UPLC/Q-TOF6550).…”
Section: Experimental Setup Of Plasma Source and Tetracycline Degrada...mentioning
confidence: 99%
“…The effects of the operating parameters such as applied voltage, pulse frequency and gas flow rate on the generation of ˙OH radicals both in gas and liquid phase were also investigated [10]. The repetitive pulsed gasliquid discharge in different working gases demonstrated that the Ar tip spark discharge could increase the plasma-liquid interaction efficiency and H 2 O 2 production was dominated by ˙OH radicals [11]. Wang and Bruggeman [12] investigated ˙OH flux and loss probability on quartz surface by microscopic LIF, boasting a spatial resolution of 10 µm to accurately resolve the near surface gradient of ˙OH radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma technology, known for its versatile discharge types, offers multiple pathways for CO 2 conversion, including corona discharge, dielectric barrier discharge (DBD), microwave plasma and gliding arc discharge [12,13]. Recently, gas-liquid discharge plasma stands out for its unique advantages, primarily its ability to generate plasma in direct contact with a liquid phase, thereby enhancing gas-liquid mass transfer and chemical reaction kinetics [14][15][16][17]. This interaction between plasma-generated species and the liquid phase facilitates the efficient production of valuable products like CO and H 2 under ambient conditions, highlighting the potential of gas-liquid discharge plasma in energy conversion endeavors.…”
Section: Introductionmentioning
confidence: 99%